Effects of exercise program on development of lower limbs' explosive strength in tennis players: a systematic review - Dordevic, S.; Velièkovic, M.; Milenkovic, S.; Milenkovic, S.; Nikolic, D.; Jezdimirovic, M. (23rd International Scientific Conference "FIS COMMUNICATION 2021", 2021)
The aim of the research was to determine the effects of exercise programs on lower limbs` explosive strength in junior tennis players. For collecting of appropriate scientific researches from 2010 till 2021 the following keywords were used: tennis, eplosive strength, training and exercise program, motor ability- in three electronic databases (Google Scholar, KobSon, SCI index). Based on the keywords, the existing scientific researches have gone through three levels of selection in order to enter the final analysis. These analyzed researches are presented through five groups of parameters: authors of the research, sample description (sex, age and number), experimental treatment (description, frequency), measuring instruments and results. Only 10 researches have met the criteria, and the analysis shown that the exercise programs lasted from 6 to 8 weeks, with weekly training frequency between two and three times of 30 minutes, that is, as an addition to the training. Exercise programs that have been used for the development of lower limbs` explosive strength in tennis players were of plyometric type, with and without equipment. The tests, by which the assessment of the lower limb` explosive strength was determined, were: CMJ, CMJ (bilateral/unilateral), SJ, DJ and OLH. The results of the applied exercise programs have shown, in all of the analyzed researches, statistically significant progress (p<0.05). A lower-limb explosive strength represents a very significant segment within the basic motor skills of tennis players in the junior category due to the latent period of development period, but also to the pretensions of the increasing dynamism of the tennis game. In accordance with this, the research can help trainers to use the information for planning the development of the explosive strength of their tennis players, and for athletes to advance and manifest the maximum potential of this part of this basic motor space.